Repliek - Woud, A. van der (BMGN - Low Countries Historical Review, 2008)
ResponseThe main theme of my book is the rapid development of a modern infrastructure for communication and mobility during the second half of the nineteenth century in the Western world in general and in the Netherlands in particular. The end-result is not an example of the history of technology in the standard sense. Rather, the book explains that the new technology fundamentally changed the idea of reality, simply because totally new standards of communication and mobility revolutionized the age-old characteristics of space and time. Its focus on the social consequences of the new technology affords the book a place between a history of technology and a history of culture: the prior history of the technological society in which we live today, where social norms and values and standards have been dominant since the middle of the nineteenth century. This response is part of the discussion forum 'Een nieuwe wereld' (A. van der Woud).